Monitoring CO2 Levels and Total Volatile Organic Compounds in Tofu Waste Composting Process Using IoT-Based Maggot Larvae - Zakaria, Ahmad; Fadela, Dian Mira; Haziman, Muhammad Luthfan; Tambunan, Jenny Anna Margaretha; Aynuddin, Aynuddin; Fachrurrazie, Fachrurrazie; Lestari, Endang Sri (Journal Of Biology Education Research (JBER), 2025)
The increasing volume of waste poses significant environmental and public health risks if not properly managed. The management of unprocessed waste may be initiated at the household level by applying principles of the circular economy. This study aims to investigate the integration of bioconversion technology using Black Soldier Fly (BSF) larvae with an IoT-based air quality monitoring system for tofu dregs waste management. A microcontroller-based device was developed to monitor and control humidity, carbon dioxide (CO₂), and Total Volatile Organic Compounds (TVOCs) using sensors and an adsorption-based scrubber system. The results indicate that CO₂ levels decreased from 1470–1747 ppm to 400–483 ppm, while TVOC levels were reduced from 163–346 ppb to 0–6 ppb after treatment, significantly improving air quality and minimizing odor emissions. The combination of BSF larvae-assisted bioconversion and automated emission control demonstrates a highly effective and sustainable approach to organic waste processing, reducing environmental pollution and generating valuable byproducts for economic utilization. This system offers a scalable solution for future applications in circular economy-based waste management.  In conclusion, this system offers a scalable solution for future applications in circular economy-based waste management.